Google top 100 simplified tips & tricks - Kraynak, Joe (Wiley Pub., 2005)
Presents a visual guide to using Google, covering such topics as search options, locating audio and video clips, using reference tools, using Froogle, posting a message to a discussion group, and creating a blog.
Includes index.
Keywords: Google; Internet searching; Web search engines